2021
DOI: 10.3389/fvets.2021.671948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet Supplementation and Age at Slaughter on Carcass Characteristics of Creole Goats

Abstract: The objective of this study was to evaluate the effects of diet and age on finishing performances and carcass characteristics of male Creole goats. A total of 91 weaned male Creole kids [84 days old ± 7 days, 9.2 kg live weight (LW) ± 0.5 kg] were randomly allocated in a 2 × 3 experimental design. The animals were fed individually with two diets: C0: a 28-day-old Digitaria decubens grass alone, or C50: the same grass plus a commercial concentrate (50% of the total diet) and then slaughtered at 7, 11, or 15 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In this study, it was found that the important tissues and organs such as muscle, visceral fat, and most of the internal organs, especially the mammary gland of dairy goats, grow faster than the body. It has been reported the fat deposition characteristics of shelter-feeding goats differ from those of grazing, with shelter-feeding goats depositing more visceral fat [ 30 , 48 ], which was due to the higher DMI and energy intake [ 30 ]. The growth exponent or slope (b-value) was greater at the 10–20 kg stage than at the 20–30 kg stage, mainly in muscle, skin and mohair, heart, spleen, lung, mammary gland, and abomasum.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the important tissues and organs such as muscle, visceral fat, and most of the internal organs, especially the mammary gland of dairy goats, grow faster than the body. It has been reported the fat deposition characteristics of shelter-feeding goats differ from those of grazing, with shelter-feeding goats depositing more visceral fat [ 30 , 48 ], which was due to the higher DMI and energy intake [ 30 ]. The growth exponent or slope (b-value) was greater at the 10–20 kg stage than at the 20–30 kg stage, mainly in muscle, skin and mohair, heart, spleen, lung, mammary gland, and abomasum.…”
Section: Discussionmentioning
confidence: 99%
“…decreases and the proportion of fat increases as body weight increases, as well as the biochemical composition of the tissues also changes, with the gain of lipids in the muscle and the loss of water, also with the advancement of maturity [14,44]. Thus, the increase in fat deposition, with the time spent in confinement, influenced the M:F ratio, which suffered a decreasing effect, as the lambs increased their weight, demonstrating that the greater the age at slaughter, the greater the weight, adiposity and carcass conformation [45,46], with weight and age at slaughter being fundamental factors that determine meat quality and make it possible to increase the adoption of strategies during decision-making that encourage the production of sheep meat and the choice of the best slaughter period according to the current needs of the Brazilian industry [38,47].…”
Section: Plos Onementioning
confidence: 99%
“…Onfarm supplementation of concentrate pellets at 1.5% of the live weight of growing kids improved growth performance, carcass traits, and provided leaner carcass (Chaudhary et al 2015). Higher level of concentrate feeding to goats increased overall carcass yields, dressing percentage, crude protein, and fat contents in meat (Kim et al 2014, Bambou et al 2021; also affected carcass traits, serum biochemical indexes, and fatty acid profiles in different muscles of female Hu lambs fed with high energy (Wang et al 2020).…”
mentioning
confidence: 99%